E-Tourism Communication: Hacking Business English Skills with Digital PBL (A Mixed-Methods Analysis) - Nadya Nurhidayah; Rusdiah Hasanuddin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study employed a Convergent Parallel Mixed-Methods design to investigate the effectiveness of Digital Project-Based Learning (DPBL) in enhancing Business English Communication (BEC) outcomes for 15 E-Tourism students (N=15) following a 12-week intervention. Quantitative results showed high agreement on Authenticity (=4.60) and Digital Proficiency (=4.53), alongside significant perceived gains in oral (=4.13) and written (=3.93) communication skills. Qualitative data confirmed DPBL acted as a rapid "hack" for skill acquisition, specifically boosting Confidence in Presentation and Professional Email Tone through constant, situated digital communication. The convergence of findings confirms that DPBL, by integrating authentic digital tools into project tasks, is a highly effective and potent pedagogical model for accelerating the development of critical BEC skills required in the E-Tourism sector for students at a Private Collage in South - Sulawesi